Problems and perspectives of financial decentralization in India - Tyapukhin, A.P.; Tasmaganbetov, A.B.; Аgleshov, К.E.; Zhanseitov, A.T. (BUKETOV BUSINESS REVIEW, 2018)
In this article, selection of an appropriate policy for government is taken into consideration to achieve some positive results through its implementation. According to authors, these results can be followed by adjusting to the situation which world brings as a result of progress. Some countries change their socialist economy to capitalization because it is not only beneficial for government and it is also trend of modern world. In this article, the concept of «Public Policy» can be exemplified by the implementation opportunity of financial decentralization in India. The authors analyze financial policy transformation in the country and challenges which faced during this reform. Referring to authors, fiscal decentralization and local governance have positive impact which can lead to development in general especially, for the case of India. This economic growth shows lower violence than before and considerable reduction in poverty. Therefore, political and economic decentralization may boost development because these can provide enough infrastructure and human resources to provide an implementation of public policy in India.